Human vs automatic advice : what’s the future of personal counselling for cosmetic products? : focus on the Portuguese market - Poças, Teresa Raquel Alves (2019)
From the studies conducted, it was observed that the cosmetic industry has shown exponential growth in recent years, and the increasing use of social networks has influenced this phenomenon. Also, they have led to changes in consumer buying behavior, including the increase in online shopping. Due to the increase in the importance of the self and the concern with having a good appearance, consumers expect more personalized service and advice. In response to these expectations, companies have invested in the pursuit of machine learning technologies. These technologies can offer automatic advice without human intervention and, at the same time, they cause changes in the purchase decision-making process. In this context, this study addresses the receptivity of these technologies in the Portuguese market, using “HiMirror” technology as a benchmark, to help companies to define their sales and marketing strategy. The Technology Acceptance Model was used as a basis for testing consumer acceptance and it was observed that consumers find this technology useful and the perception of utility positively influences their propensity to use it in-store. Personality traits, such as creativity, fashion sense, and rationality, were analyzed to find clusters about the intention to use this technology and to find the best target for these services. Finally, it was analyzed in which buying situations and for what kind of products consumers prefer to be advised by machines rather than humans.